Penanaman Nilai-Nilai Akhlak pada Anak (Studi kajian secara umum pada Quran Surah Luqman) - Irsal Irsal (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: This article discusses how Luqman Al-Hakim is a role model in character building in children. The results of this study indicate that Luqman al-Hakim in the Qur'an is contained in a surah that is attributed to his name. His name is famous because in the Qur'an there are many teachings and advice to his children in their relationship with Allah (vertical interaction), as well as with fellow humans (horizontal interaction). Ahmad Musthafa Al Maraghi also explained that the asbabun nuzul of the revelation of Surah Luqman Al- Hakim was when the Quraish people asked the Prophet Muhammad about the teachings and example of Lukman Al-Hakim to his son and his son's obedience and obedience to his father's teachings. The implications of Islamic educational values contained in Luqman's letter make the formation of an Islamic personality one of the options to protect children as early as possible from negative environmental influences. The formation of a child's personality is in principle an ongoing process. The process will be better and more successful when parents can combine two factors, namely the preparation factor functions as a process of forming a child's personality before he is born into the world (prenatal), and the implementation factor functions as a process of forming a child's personality after he is born, through formal education and non-formal education. To realize the formation of an Islamic personality both personally and socially.Keywords: Luqman Al-Hakim, Surah Luqman, instilling moral values. Abstrak: Artikel ini membahas tentang cara luqman Al-hakim sebagai tauladan dalam pembentukan karakter pada anak.. Hasil penelitian ini menunjukkan bahwa Luqman al-Hakim didalam Al-Quran termuat dalam surah yang dinisbatkan kepada namanya. Namanya terkenal sebab didalam Al-Quran banyak ajaran-ajaran dan nasihat-nasihatnya kepada anak nya dalam hubungan dengan Allah (interaksi vertikal), maupun dengan sesama manusia (interaksi horizontal). Ahmad Musthafa Al Maraghi juga menjelaskan bahwa asbabun nuzul turunnya surah Luqman Al-Hakim adalah tatkala kaum Quraish bertanya kepada Nabi Muhammad mengenai ajaran dan teladan Lukman Al-Hakim kepada anaknya dan kepatuhan dan ketaatan anaknya kepada ajaran ayahnya. Implikasi nilai-nilai pedidikan Islam yang terkandung dalam surat Luqman tersebut, menjadikan pembentukan kepribdian yang Islami sebagai salah satu pilihan guna membentengi anak sedini mungkin dari pengaruh lingkungan yang negatif. Pembentukan kepribadian anak pada prinsipnya merupakan proses yang berkelanjutan. Proses tersebut akan lebih baik dan berhasil manakala para orang tua dapat mengkombinasikan dua faktor, yaitu faktor persiapan berfungsi sebagai proses pembentukan kepribadian anak sebelum ia lahir di dunia (prenatal), dan faktor pelaksaan berfungsi sebagai proses pembentukan kepribadian anak setelah ia lahir,melalui pendidikan formal dan pendidikan nonformal. Untuk merealisasikan pembentukan kepribadian yang islami baik secara personal maupun sosial.Kata kunci: Luqman Al-Hakim, Surah Luqman, penanaman nilai akhlak.